Polimorfisme Gen Glutamylcysteine Ligase Catalytic (GCLC) Sebagai Deteksi Kerentanan Pasien Tuberkulosis Terhadap Stres Oksidatif Akibat Infeksi Mycobacterium tuberculosis - Andi Zulkifli AS; Muh. Nasrum Massi; Rosana Agus (Universitas Hasanuddin, 2021)
The important genetic factor about susceptibility of oxidative stress in Pulmonary Tuberculosis (PTB) has not been determined. The aim of this study was to analyse the association between polymorphism glutamatecysteine ligase catalytic subunit (GCLC) genes with susceptibility of oxidative stress in PTB in Makassar population of Indonesian. The Methods use is a case-control study was performed on 25 paired subjects with or without PTB, These subjects were selected from result of BTA stain from sputum subjects. The following polymorphisms were genotyped by PCR-RFLP of −129C/T in the GCLC gene. Genotype frequencies and allelic frequencies were analysed. The Results was found There were significant differences in the distribution of genotype frequencies for polymorphism −129C/T in GCLC gene between PTB and non-PTB subjects. The distribution of the allelic frequencies of these genes also showed significant difference between the two groups. Conclusions is The genetic polymorphisms in GCLC −129C/T are associated with susceptibility of Oxidative stress on PTP subject.